2017
DOI: 10.1002/bies.201600248
|View full text |Cite
|
Sign up to set email alerts
|

Cell reintegration: Stray epithelial cells make their way home

Abstract: Ongoing work shows that misplaced epithelial cells have the capacity to reintegrate back into tissue layers. This movement appears to underlie tissue stability and may also control aspects of tissue structure. A recent study reveals that cell reintegration in at least one tissue, the Drosophila follicular epithelium, is based on adhesion molecules that line lateral cell surfaces. In this article we will review these observations, discuss their implications for epithelial tissue development and maintenance, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Thus, it is possible that daughter cells could either differentiate following divisions or alternatively, reintegrate into the basal layer following mitosis. Such behaviors have been recently documented in other epithelia (McKinley et al, 2018; Wilson & Bergstralh, 2017), and dedifferentiation has been reported following wounding in adult skin (Donati et al, 2017). However, it has not been technically possible to follow daughter cell fates long term following cell division with ex vivo imaging of embryonic explants.…”
Section: Resultsmentioning
confidence: 65%
“…Thus, it is possible that daughter cells could either differentiate following divisions or alternatively, reintegrate into the basal layer following mitosis. Such behaviors have been recently documented in other epithelia (McKinley et al, 2018; Wilson & Bergstralh, 2017), and dedifferentiation has been reported following wounding in adult skin (Donati et al, 2017). However, it has not been technically possible to follow daughter cell fates long term following cell division with ex vivo imaging of embryonic explants.…”
Section: Resultsmentioning
confidence: 65%
“…Cell reintegration is a relatively recently identified morphogenetic cell behaviour that appears to be a fundamental, conserved morphogenetic process [42]. Through live imaging and genetic studies in Drosophila epithelial tissues, it was shown that daughter cells born apically or basally displaced from a tissue layer are able to (re)integrate back into the layer [42,131]. The IgCAMs Nrg and Fas2 are regulators of cell reintegration in Drosophila epithelia [42].…”
Section: Reintegration (A) Neuroglian and Fasciclinmentioning
confidence: 99%
“…Cell reintegration is proposed to be driven by the energyfavourable tendency to maximize cell-cell adhesion along the lateral surface [42,131]. This model to explain reintegration can be pictured as 'zipping up', where the rapid expansion of cell-cell contact is driven by the formation of homophilic adhesions between IgCAM molecules, acting as the teeth of a zipper.…”
Section: Reintegration (A) Neuroglian and Fasciclinmentioning
confidence: 99%
“…Convergent extension, which involves the exchange of cell boundaries, alters the aspect ratio of growing embryos (Sutherland et al, 2020). Intercalation of individual cells into a pre-existing epithelial layer has been described in epiboly and keel formation during zebrafish development, the developing murine ureteric bud, multiciliated cell development in Xenopus embryo, and in the extending branches of mammary organoids in 3D culture (Bruce and Heisenberg, 2020; Geldmacher-Voss et al, 2003; Neumann et al, 2018a; Packard et al, 2013; Stubbs et al, 2006; Wilson and Bergstralh, 2017). Moreover, re-integration of extruded cells has been observed in the Drosophila follicular epithelium (Bergstralh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%